Análise da evolução patológica da paracoccidioidomicose pulmonar experimental após inibição do receptor P2x7 - Cecatto, Vanessa (2019)
Introduction: Paracoccidioidomycosis, caused by a fungus in the genus Paracoccidioides. The states of the South and Southeastern regions of Brazil concentrate most of the cases of this disease, highlighting Paraná with the majority of PCM deaths in the South. This systemic mycosis generates a serious public health problem due to its incapacitating potential and affects especially the lungs. Sometimes the treatment of this disease becomes long and difficult to continue. Previous studies demonstrated that inhibition of the P2X7 receptor has beneficial effects against the disease. This study was conducted to assess the effects of P2X7 receptor inhibition by brilliant blue G (BBG) dye in a pulmonary paracoccidioidomycosis experimental model. Methods: Thirty male rats were divided into five groups: absolute control group, negative control group, experimental group 50, experimental group 100, and experimental group 150. The last four groups underwent experimental induction of pulmonary paracoccidioidomycosis; however, only the brilliant blue G experimental groups 50, 100, and 150 were administered BBG intraperitoneally every 48 h at doses of 50, 100, and 150 mg/kg respectively, to inhibit P2X7 receptor activity. To assess the effects of this treatment, lung tissue was analyzed histologically and the levels of the anti-gp43 antibody were measured by enzyme-linked immunosorbent assay. Results: Lung biopsies of the animals treated with BBG exhibited a significant reduction in the number and area of granulomas. In addition, comparing the groups, it was possible to observe effectively lower anti-gp43 antibody values in the groups receiving BBG treatment. Conclusions: Treatment with BBG reduced the number and area of granulomas in the lung tissue and levels of anti-gp43 antibodies against Paracoccidioides brasiliensis, thereby mitigating pulmonary paracoccidioidomycosis in the experimental model.